Special pedagogy in the context of contemporary theory of education - Amadeusz Krause (Studia z Teorii Wychowania)
The text presents the link between special pedagogy and the theory of education. The basic questions asked are what are the reflections in this scientific sub-discipline on the educational impact concerning a person with disabilities? A well-known problem in special pedagogy is the dominance of rehabilitation and therapy in working with the child. The question is whether this affects the issues of educating such a child in the context of limiting his or her autonomy and right of emancipation. The article considers the adaptation and emancipation balance in the education of a child with a disability.